Entomophily, Ornithophily and Anemochory in the Highly Self-incompatible Boswellia ovalifoliolata Bal. & Henry (Burseraceae), an Endemic and Endangered Medicinal Tree Species: Entomophily and Anemochory in Boswellia ovalifoliolata - Solomon Raju, Aluri Jacob; Lakshmi, Pakkurti Vara; Ramana, Kunuku Venkata (Biological Sciences - PJSIR, 2013)